Turkey : Forestry Sector Review - World Bank (Washington, DC, 2013)
The report identifies the challenges, and opportunities the forestry sector faces in Turkey, where twenty five percent of the country's land area is covered by forests, with significant economic, environmental, and cultural functions. The challenges identified in the review include poverty, land tenure, the need to establish multi-purpose, participatory forest management planning, and, to control soil erosion in degraded areas, including the need to restore the sector's financial viability. Following an introductory review on economic growth, urbanization, and new demands on forest resources, the study analyzes the liberalization of the policy framework, the reform of state-owned enterprises, and the public expenditure restraints. The sustained realization of forestry development goals in the context of strengthened economic discipline, should lead to the planning, and management of forest resources at both the national, and local levels; to a decrease in forest areas managed primarily for wood production; to an expansion of protected areas, and national parks, covering a wide range of Turkey's natural ecosystems; and, to reforestation levels rising significantly the degraded forest lands, supported by active communal participation. This will be achieved based on suggestions on policies, and institutional arrangements, and on consensus development on sectoral priorities. Recommendations suggest pilot approaches to biodiversity conservation; reconsideration of public sector agencies' organizational structures; integrated rural development initiatives to support poverty alleviation, including institutional target programs for the poorest forest-dependent people; and, development of community based resource management approaches, mainstreamed through supportive regulations, guidelines, and budgetary processes.